2005
DOI: 10.4049/jimmunol.174.3.1751
|View full text |Cite
|
Sign up to set email alerts
|

One NY-ESO-1-Derived Epitope That Promiscuously Binds to Multiple HLA-DR and HLA-DP4 Molecules and Stimulates Autologous CD4+ T Cells from Patients with NY-ESO-1-Expressing Melanoma

Abstract: NY-ESO-1 is expressed by a broad range of human tumors and is often recognized by Abs in the sera of cancer patients with NY-ESO-1-expressing tumors. The NY-ESO-1 gene also encodes several MHC class I- and class II-restricted tumor epitopes recognized by T lymphocytes. In this study we report one novel pan-MHC class II-restricted peptide sequence, NY-ESO-1 87–111, that is capable of binding to multiple HLA-DR and HLA-DP4 molecules, including HLA-DRB1*0101, 0401, 0701, and 1101 and HLA-DPB1*0401 and 0402 molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
60
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 19 publications
4
60
1
Order By: Relevance
“…We found no evidence of class I restriction in any CD4 þ clone as has been described previously Mitchell et al, 1993;Darrow et al, 1996). Restriction of MAGE epitopes via non-HLA-DR class II molecules as described previously is a more likely explanation for our findings (Schultz et al, 2000;Mandic et al, 2005). None of the CD4 þ T-cell clones established in this study secreted interferon-g in response to recipient-derived nonmelanoma cells.…”
Section: Discussionsupporting
confidence: 77%
“…We found no evidence of class I restriction in any CD4 þ clone as has been described previously Mitchell et al, 1993;Darrow et al, 1996). Restriction of MAGE epitopes via non-HLA-DR class II molecules as described previously is a more likely explanation for our findings (Schultz et al, 2000;Mandic et al, 2005). None of the CD4 þ T-cell clones established in this study secreted interferon-g in response to recipient-derived nonmelanoma cells.…”
Section: Discussionsupporting
confidence: 77%
“…1, 2 and unpublished data). This is at variance with studies showing that in patients with ESO + malignancies the frequencies of CD4 + T cells specific for these epitopes are similar (27,28,37). This might be explained by the fact that the DCs that prime CD4 + T cells generate and present biased repertoires of ESO peptides, thus obscuring the actual immunogenicity of the peptides.…”
Section: Discussioncontrasting
confidence: 52%
“…It is a cytosolic protein of 180 aa, and MHC I and MHC II epitopes have been extensively mapped (http://www.cancerimmunity.org/ peptidedatabase/Tcellepitopes.htm). For A2 the immunodominant epitope is 157-165 (157p), which is expressed by most tumor cells (2,3,26), and for DR1 various epitopes have been reported, for example, 123-137 (123p), 87-101 (87p), and 87-111 (27,28). Our investigations in this highly defined system showed that 1) efficient priming of CD8 + T cells in draining lymph nodes requires available Th1 cells and copresentation of strongly immunogenic MHC I and MHC II epitopes by the same mature DC; 2) the Th1 cytokines IL-2 and IFN-g, namely in combination, induce CCR5 surface expression on naive CD8 + T cells; 3) the chemokines CCL4 and CCL3 play differential roles in guiding Th1 cells to DCs and activated naive CD8 + T cells to DC-CD4 T cell conjugates, respectively; and 4) these chemoattractions and the strength of Th1 cell help determine the upregulation of S1P 1 on freshly primed CD8 + T cells and hence their exit from the draining lymph nodes into circulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that CGA-derived epitopes that represent tumor-specific T cell targets (27), give rise to spontaneous Th1-type CD4 + T cells isolated either from PBLs or TILs of cancer patients (24,28). However, such spontaneous CD4 + T cell responses are found in patients with progressive disease, questioning their role in promoting potent antitumor CTL functions.…”
Section: Discussionmentioning
confidence: 84%